Experience with Groin Flap As A Cover for Hand and Fore-Arm - S. C. Bhatia; K. L. Takkar; J. L. Gupta (Indian Journal of Plastic Surgery, 1976)
This paper described our experience with groin flap as a full thickness cover for hand and lower forearm and in the reconstruction of first web. Advantages of groin flap in comparision to direct flaps, tube pedicle and the deito-pectoral flap have been discussed. Steps of the operative technique and the stages of transfer have been described.